Sodium reduction in Turkey breast meat by using sodium anion species. (April 2020) - Pandya, Janam K.; Decker, Kelsey E.; Goulette, Timothy; Kinchla, Amanda J.
Abstract: Diets high in sodium increases blood pressure linked to the risk of heart disease and stroke. While there are many reduced sodium products in the marketplace, consumer acceptability of reduced and/or low sodium foods remains a challenge. This study aims at reducing the overall sodium content in turkey meat application by using alternative sodium species. Initial experiments studied the sodium absorption across the temperature range of 4 to 90 °C which showed higher sodium content for thermally processed samples over a longer cooking time. Overall, the adsorption rate was found to be slower and was not affected by protein denaturation. Additional experiments studied the sodium diffusion by replacing sodium chloride with alternative sodium salts with comparatively larger anions, which resulted in, 20–46% reduction in overall sodium content of thermally processed turkey cubes. A sensory test conducted amongst 46 untrained panelists evaluated consumer "liking" of the turkey meat cooked in 20 g/L of sodium chloride, disodium phosphate and 50:50 g:g blend solution of both sodium salts. The acceptability test resulted in higher overall liking of the partially reduced salt sample compared to the control. Highlights: Sodium diffusion rate in protein model is relatively slower. Longer (>40 min) thermal treatment allows significantly higher sodium absorption. Sodium salts with larger anions reduces sodium adsorption up to 46% in turkey meat. Partial replacement of NaCl with Na2 HPO4 reduced the sodium content by 20%. Partial replacement of NaCl with Na2 HPO4 showed better consumer acceptability.